RFID Transponder Collision Control Algorithm - Reza, Ahmed Wasif; Tan, Kim Geok; Kiew, Joh Chia; Dimyati, Kaharudin (Springer US, 2011)
Transponder collision problem can be significant when a large number of RFID (radio frequency identification) transponders exist in field. Most existing anti-collision algorithms can solve this problem. However, problem arises when all or part of these transponders are having identical UID (unique identification). This paper proposes a new transponder collision control algorithm to overcome overlapping that occurs among transponders with identical UID in RFID large scale deployment (e.g., in a large warehouse), so that the RFID reader can successfully identify the quantity of transponders for each particular UID with high identification accuracy. The proposed anti-collision algorithm adopts a modified version of frequency domain method by adding stochastic delays in time domain. The obtained results show that the proposed method can achieve optimum frequency bandwidth utilization and at the same time poses high identification accuracy (almost 100%) with low identification delay.